2016
DOI: 10.1038/ncomms10407
|View full text |Cite
|
Sign up to set email alerts
|

Using synthetic bacterial enhancers to reveal a looping-based mechanism for quenching-like repression

Abstract: We explore a model for ‘quenching-like' repression by studying synthetic bacterial enhancers, each characterized by a different binding site architecture. To do so, we take a three-pronged approach: first, we compute the probability that a protein-bound dsDNA molecule will loop. Second, we use hundreds of synthetic enhancers to test the model's predictions in bacteria. Finally, we verify the mechanism bioinformatically in native genomes. Here we show that excluded volume effects generated by DNA-bound proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 59 publications
(77 reference statements)
2
15
0
Order By: Relevance
“…2A. The data show that in the elastic regime (L ≤ b), protrusions bound in-phase with δr (solid lines, ↑) strongly reduce the looping probability relative to that of the bare DNA, while protrusions positioned out-of-phase to δr (dashed lines, ↓) increase the looping probability, as we showed previously (37). However, in the entropic regime (L b), all chains converge to values of F…”
Section: Long-range Down-regulatory Effectsupporting
confidence: 63%
See 3 more Smart Citations
“…2A. The data show that in the elastic regime (L ≤ b), protrusions bound in-phase with δr (solid lines, ↑) strongly reduce the looping probability relative to that of the bare DNA, while protrusions positioned out-of-phase to δr (dashed lines, ↓) increase the looping probability, as we showed previously (37). However, in the entropic regime (L b), all chains converge to values of F…”
Section: Long-range Down-regulatory Effectsupporting
confidence: 63%
“…Our work indicates that we should consider three ranges for the physics of looping of chromatinized DNA. For short ranges which we studied previously (14,37), looping is dominated by elastic energy. As shown in this work, there is an intermediate entropic looping range of up to ∼10 kbp of bare DNA (or ∼100 kbp of "mixed" DNA).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Studies exploring the formation of this repression loop have found that it is heavily dependent on the spacing of the LacI operator sites relative to each other [28][29][30] . Due to the helical nature of B-form DNA, which completes a full rotation roughly every 10.5 bp, as operator sites are placed at various distances from one another along the DNA this also changes their relative orientation along the face of the DNA helix.…”
Section: Repression By Transcription Factors Is Dependent On Operatormentioning
confidence: 99%